Emaranhamento genuínos nas variáveis espaciais de sistemas tripartidos e quadripartido de fótons - Gonçalves Netto, Victor (2020)
This dissertation deals with the genuine entanglement in the spatial variables of a tripartite photon system and of a quadripartite photon system. Each term used in the previous sentence was investigated during the course of this work and the first chapters of this dissertation are reserved to discuss the meaning of these terms. The photon states are reached with the use of an experimental scheme that uses the spontaneous parametric down-conversion, SPDC. We dedicate a few pages to deal with SPDC, but with one goal in mind: to obtain the tripartite state of photons. These states is then submitted to the van Loock-Furusawa entanglement criterion, confirming that, under certain conditions, genuine entanglement occurs.